Taras Shevchenko Translated and Retranslated by Vera Rich: A Lifelong Search for Poetic Perfection - Kolomiyets, Lada (Respectus Philologicus, 2018)
[full article and abstract in English] The article deals with the translator’s laboratory of Faith Elizabeth Joan Rich, better known by her pen name Vera, which is the direct Ukrainian translation of Faith. The discussion focuses on post-publication self-revisions by Rich of her earlier translations from “The Kobzar” by the Ukrainian Romantic poet Taras Shevchenko (1814–1861) in subsequent printings, as well as on her reprinted and new translations of Shevchenko. The article details the numerous instances of self-editing by the translator, including two versions of the poem «Садок вишневий коло хати…» (“Beside the house, the cherry’s flowering…” and “Cherry-trees bloom by the house yonder…”). It also analyses the singability of translations by Rich, and in particular of the verses “Roaring and groaning rolls the Dnipro…” and “O my thoughts, my heartfelt thoughts, I am troubled for you…” The article concludes that in her strategy Rich has developed a holistic approach to translating Shevchenko’s “Kobzar”.